We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
180
1
avatar

Let $f(x)=x+2$ and $g(x)=x/3.$ Also denote the inverses to these functions as $f^{-1}$ and $g^{-1}.$ Compute \[f(g^{-1}(f^{-1}(f^{-1}(g(f(19)))))).\]

 Mar 20, 2018
 #1
avatar+7545 
+3

\(f(x)=x+2\)          and          \(f^{-1}(x)=x-2\)

\(g(x)=x/3\)             and          \(g^{-1}(x)=3x\)

 

There may a better way to do this, but here is what I got:

 

\(\begin{array}\ &&f(g^{-1}(f^{-1}(f^{-1}(g( {\color{Red}f(19)} ))))) \\ =&&f(g^{-1}(f^{-1}(f^{-1}(g( {\color{Red}19+2} )))))\\ =&&f(g^{-1}(f^{-1}(f^{-1}(g( {\color{Red}21} )))))\\ =&&f(g^{-1}(f^{-1}(f^{-1}( {\color{Orange}g( 21 )} ))))\\ =&&f(g^{-1}(f^{-1}(f^{-1}( {\color{Orange}21/3} ))))\\ =&&f(g^{-1}(f^{-1}(f^{-1}( {\color{Orange}7} ))))\\ =&&f(g^{-1}(f^{-1}( {\color{orange}f^{-1}(7)} )))\\ =&&f(g^{-1}(f^{-1}( {\color{orange}7-2} )))\\ =&&f(g^{-1}(f^{-1}( {\color{orange}5} )))\\ =&&f(g^{-1}( {\color{Green}f^{-1}( 5 )} ))\\ =&&f(g^{-1}( {\color{Green}5-2} ))\\ =&&f(g^{-1}( {\color{Green}3} ))\\ =&&f({\color{Blue}g^{-1}( 3 )})\\ =&&f({\color{Blue}3(3)})\\ =&&f({\color{Blue}9})\\ =&&{\color{Fuchsia}f(9)}\\ =&&{\color{Fuchsia}9+2}\\ =&&{\color{Fuchsia}11} \end{array}\)

.
 Mar 21, 2018
edited by hectictar  Mar 21, 2018
edited by hectictar  Mar 21, 2018

38 Online Users

avatar
avatar
avatar